2021
DOI: 10.1515/epoly-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of two high polymers suspended in an abrasive slurry jet

Abstract: With high polymer added into suspension, the use of abrasive slurry jet (ASJ) has significant advantages in energy management. The quality and efficiency of ASJ are affected distinctly by its structure and the flow field feature, both of which depend on the rheological properties of the abrasive slurry. Therefore, this paper carries out a series of experiments to study the rheological properties of abrasive slurry with polyacrylamide (PAM) and carboxy methyl cellulose (CMC) commonly used in ASJ. The paper also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Carboxymethylcellulose (CMC) is another popular additive that can be used to modify viscosity. 90 X. Wang et al conducted some investigations on rheological properties of PAM and CMC 91 and reported jet with CMC additive had higher apparent viscosity under the same shear rate and concentration. Some previous studies showed that the CMC-added AWJs have shown low settling-time.…”
Section: Carboxymethylcellulosementioning
confidence: 99%
“…Carboxymethylcellulose (CMC) is another popular additive that can be used to modify viscosity. 90 X. Wang et al conducted some investigations on rheological properties of PAM and CMC 91 and reported jet with CMC additive had higher apparent viscosity under the same shear rate and concentration. Some previous studies showed that the CMC-added AWJs have shown low settling-time.…”
Section: Carboxymethylcellulosementioning
confidence: 99%
“…The various types of fluids currently known, of natural or synthetic origin, from the point of view of rheology, are called Newtonian and non-Newtonian; the latter characterizes most known fluids, and their relationship with shear stress and shear rate is not constant. PVA is a non-Newtonian fluid whose rheological behavior is independent of time [ 22 ]. In general, rheology is the science that studies the deformation of a fluid when it is subjected to external forces, be it compression or shear forces [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The polymers are long-chained molecules that impart a viscoelastic fluid behaviour to the suspension mixture. There are various polymer additives during the Suspension-type AWJ machining of several materials, including SUPER-WATER/polyacrylamide (PAM) [15][16][17], Xanthan [16,18], polyox [19], carboxy methyl cellulose (CMC/ cellulose gum) [16,17] and others. Recently, Wang et al [20] studied the rheological properties of the suspension mixture with PAM and CMC used in suspension-type AWJs.…”
Section: Introductionmentioning
confidence: 99%
“…There are various polymer additives during the Suspension-type AWJ machining of several materials, including SUPER-WATER/polyacrylamide (PAM) [15][16][17], Xanthan [16,18], polyox [19], carboxy methyl cellulose (CMC/ cellulose gum) [16,17] and others. Recently, Wang et al [20] studied the rheological properties of the suspension mixture with PAM and CMC used in suspension-type AWJs. The authors concluded that the abrasive does not influence the apparent viscosity of the slurry mixture.…”
Section: Introductionmentioning
confidence: 99%